COVID-19 and Religious Practices: A Case Study of the Cham in Ninh Thuan - Pham Thi Thanh Huyen (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
With the ups and downs of the COVID-19 pandemic, including waves of infections, the discussion and questioning of how to adapt traditional and religious activities in times of crisis became of upmost importance among the clerics of religious groups in Ninh Thuan. This article discusses the impact of the COVID-19 pandemic on the Cham in Ninh Thuan, the role of faith agents in responding to the unprecedented health crisis, and the way they maintained their faith and kept the spirit of traditions and religions alive during a difficult time. At the same time, this article looks into how the religious communities in Ninh Thuan engaged in dialogue about the COVID-19 pandemic, including potential racial or sectarian debates, to minimize misunderstandings and mobilize resources to help each other overcome challenges and possible discrimination. This is a case study of an ethnic minority and sheds light on the flexible and resilient approaches of the Cham to navigate the pandemic and maintain their traditions and practices. This research speaks to policy-makers and provides lessons for managing crises in the future. Received 15th April 2024; Revised 5th May 2024; Accepted 7th July 2024